Abstract 022: Acute Kidney Injury in Subarachnoid Hemorrhage: Exploring its Clinical Significance and Prognostic Implications - Galadu Subah; Lee Hecht; Bridget Nolan; Aiden Lui; Anaz Uddin; Christina Ng; Nitesh Damodara; Chirag Gandhi; Fawaz Al‐Mufti (Stroke: Vascular and Interventional Neurology)
Introduction Subarachnoid Hemorrhage (SAH) resulting from the spontaneous rupture of an aneurysm is a rare and highly debilitating condition. Despite its severity, patients with aneurysmal SAH remain understudied, particularly concerning the evaluation of the incidence and consequences of subsequent acute kidney injury (AKI). Thus, the objective of this study was to explore the predictors and ramifications of AKI in patients with aneurysmal SAH. Further research and attention to this area are crucial for improving patient outcomes and guiding clinical interventions in this challenging condition. Methods ICD‐10‐CM codes were used to query the National Inpatient Sample (NIS) for patients with AIS between 2010 and 2019. Subgroup analysis was stratified by the presence of a definitive AKI diagnosis. The AKI and non‐AKI groups were assessed for baseline clinical characteristics, interventions, complications, and outcomes. Descriptive statistics, multivariate regressions, and propensity score‐matching were all performed using IBM SPSS 28. Results 76,553 patients within the NIS were diagnosed with nontraumatic SAH between 2010 and 2019, of which 10,634 (13.89%) had a comorbid diagnosis of AKI. Patients with AKI were on average older (63.29 vs 61.07, p < 0.01), more often obese (12.15% vs 9.32%, p < 0.01), of the white race (55.82% vs 51%, p < 0.01), and considered long‐term users of anticoagulants (8.12% vs 5.34%, p < 0.01) when compared to the non‐AKI group. In terms of complications, patients within the AKI cohort had lower rates of decompressive hemicraniectomy (1.37% vs. 2.38%, p = 0.52) and, interestingly, cerebral vasospasms (4.47% vs. 8.22%, p < 0.01). However, AKI patients had higher rates of deep vein thrombosis (6.36% vs. 3.54%, p < 0.01), pulmonary embolism (4.22% vs. 1.42%, p < 0.01), pneumonia (21.39% vs. 8.84%, p < 0.01), urinary tract infection (19.07% vs. 13.32%, p < 0.01), sepsis (20.27% vs. 4.18%, p < 0.01), acute myocardial infarction (12.14% vs. 3.21%, p < 0.01), and cardiac arrest (10.25% vs. 3.23%, p < 0.01). In a multivariate regression assessing the impact of AKI on SAH outcome, this diagnosis was found to be independently correlated with poor functional outcome (OR: 3.306, CI: 3.11 – 3.513, p < 0.001) above average LOS (OR: 1.503, CI: 1.438 ‐ 1.571, p <0.001), and in‐hospital mortality (OR: 2.434, CI: 2.323 ‐ 2.55, p <0.001), when controlling for admission age, SAH severity, and other significant comorbidities. Conclusion The findings of this national database evaluation reveal a significant association between AKI and adverse outcomes in patients with aneurysmal SAH. Specifically, the study highlights a strong correlation between AKI and heightened complication rates, poor functional outcome, extended hospital stays, and elevated mortality rates. These results emphasize the importance of early detection and proactive management of AKI in SAH patients to improve their overall prognosis and enhance their chances of recovery.